Islands, law and context : the treatment of islands in international law - Evans, Malcolm D.; Lewis, Reece (United Kingdom: Edward Elgar Publishing, 2023)
'This ground-breaking book challenges legal orthodoxy, presenting an original approach to the treatment of islands in international law. It offers a new perspective on how to define islands in international law, questioning how they differ from other maritime features. It focuses on the contextual factors that bear upon the legal treatment of islands, recognising that, in practice, islands have varied and unequal impacts and arguing that greater focus on context is needed to understand legal outcomes, particularly those concerning maritime boundary delimitation. Addressing the impact of rising sea levels on the interests and rights of islands and the increasing construction of artificial islands, the authors make the case for a major change in approach to the topic. This book offers international lawyers a thought-provoking reappraisal of a vital issue. It will be a useful resource for human geography and international relations scholars wishing to deepen their understanding of a key politically-contested and increasingly pressing debate in international law'--
Includes bibliographical references and index. (200-208 pages)
Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Innowawasan
Keywords: Islands -- Law and legislation; International law